Platelet donor selection for HLA‐immunised patients; the impact of donor‐specific HLA antibody levels. Issue 5 (6th April 2017) - Linjama, T.; Niittyvuopio, R.; Tuimala, J.; Pyörälä, M.; Rintala, H.; Rimpiläinen, J.; Kauppila, M.; Peräsaari, J.; Juvonen, E.
SUMMARY: Background: Approximately 20% of patients with a recurrently poor platelet transfusion increment show human leukocyte antigen (HLA) alloantibodies. The aim of this study was to analyse the impact of mean fluorescence intensity (MFI) levels of donor‐specific HLA antibodies and the feasibility of the HLAMatchmaker algorithm in donor selection. Study design and methods: A total of 270 HLA‐typed platelet transfusion responses of 40 patients were included in the study. The patients' immunisation status was determined with Luminex‐based methods, and HLA alloantibody strengths were defined as the MFI. For the Matchmaker eplet matching, the HLA‐ABC Eplet Matching Version 2.1 was used. Results: In 62% of the 270 transfusions, HLA antibodies against the transfused platelets were present, with a median cumulative MFI level of 2026 (range: 299–29 203). In multivariate analysis, a cumulative MFI level higher than 1000 emerged as an independent risk factor for a poor platelet transfusion increment, along with infection and the age of the product. Conclusion: The HLAMatchmaker algorithm alone is not a sufficient tool for donor selection. Donor selection based primarily on the levels of donor‐specific HLA antibodies is a preferable practice.